2021
DOI: 10.1177/1368430220959451
|View full text |Cite
|
Sign up to set email alerts
|

National narcissism and support for voluntary vaccination policy: The mediating role of vaccination conspiracy beliefs

Abstract: We investigate the relationship between vaccination hesitancy and the way people feel about their national groups. Antivaccination attitudes are associated with conspiracy beliefs, which have been linked to group-based defensiveness. Thus, we hypothesized that defensiveness about one’s national identity, operationalized as collective narcissism measured in relation to one’s national group, might be related to antivaccination attitudes. We found that national narcissism, but not national identification, predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 68 publications
(148 reference statements)
5
55
1
2
Order By: Relevance
“…Thus, it seems that only defensive type of national identity, which is associated with sensitivity to intergroup threats [19], fosters conviction that there is an evil outgroup that secretly uses COVID-19 vaccines for their own nefarious purposes. In such a way, our investigations corroborated and extended previous findings linking national narcissism to vaccination conspiracy beliefs [22] in a different context. We showed that national narcissists are not only more prone to believe in conspiracy theories, but also that due to these beliefs, they are less willing to vaccinate against COVID-19.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, it seems that only defensive type of national identity, which is associated with sensitivity to intergroup threats [19], fosters conviction that there is an evil outgroup that secretly uses COVID-19 vaccines for their own nefarious purposes. In such a way, our investigations corroborated and extended previous findings linking national narcissism to vaccination conspiracy beliefs [22] in a different context. We showed that national narcissists are not only more prone to believe in conspiracy theories, but also that due to these beliefs, they are less willing to vaccinate against COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…This usually leads to an appraisal of the world as a dangerous and nefarious place, and a search for imaginary enemies (i.e., alleged conspirators) that could be blamed for the ingroup's misfortunes [19]. In line with this logic, Cislak and colleagues [22] found that defensiveness about one's nationality, operationalized as national narcissism, predicted vaccination conspiracy beliefs, which further led to lower support for a voluntary vaccination policy. In such a way, due to exaggerating feelings of intergroup threat coming from higher-status groups (e.g., scientists or pharmaceutical companies), national narcissists were found to perceive the world as a dangerous place, seize on conspiracy beliefs, and in turn score higher on vaccine hesitancy.…”
Section: Covid-19 Vaccine Conspiracy Beliefs-causes and Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, instead of analyzing whether a particular conspiracy theory is true or false, social scientists usually try to understand the role of adopting such beliefs in dealing with distress (e.g., Marchlewska et al, 2021 ), self-evaluation problems ( Cichocka, Marchlewska, & Golec de Zavala, 2016 ) uncertainty ( Marchlewska et al, 2018 ), or other types of psychological weaknesses (for a review see Biddlestone et al, 2021 ). They also explore potential consequences of adopting conspiratorial explanations (e.g., the relationship between vaccination conspiracy beliefs and lower support for voluntary vaccination policy; Cislak et al, 2021 ). In a similar vein, recent research has shown that the endorsement of conspiracy theories regarding COVID-19 is negatively related to the adherence to epidemiological safety guidelines ( Kowalski et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, vaccine uptake has generally been lower than the EU average ( Vaccines Today, 2021 ): a trend that has been attributed to national narcissism (a form of national defensive identity that aims to solidify some national ideal and desires special treatment for the nation). Vaccines are often portrayed in the country as tools used by foreign agents to undermine the nation, thereby heightening vaccine hesitancy ( Cichocka et al, 2021 ; Cislak et al, 2021 ; Sternisko et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%